2021
DOI: 10.1016/j.jpsychores.2021.110552
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on mental health according to prior depression status: A mental health survey of community prospective cohort data

Abstract: Objective We aimed to investigate the mental health impact of COVID-19 on a demographically well-characterized population cohort by gender and previous depression status. Methods Among people who participated in a community cohort study between 2013 and 2018 with previous depression measurement, a total of 1928 people without quarantine experience (680 men and 1249 women) were included after responding to an online survey in March 2020. In the 2020 survey, people were q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…During the pandemic, those with low collective self-esteem, low responsibility, and low openness to experience have higher levels of economic anxiety, as do those with high levels of neuroticism, perceived vulnerability to illness, and attribution from large group activities ( Mann et al, 2020 ). People with mental and physical health conditions may have higher levels of depression and anxiety because they are more likely to be unemployed and are prone to have higher levels of depression and anxiety ( Hao et al, 2020 ; Kwong et al, 2020 ; Jung et al, 2021 ). Extreme loneliness is the main cause of psychological distress ( Mikocka-Walus et al, 2021 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, those with low collective self-esteem, low responsibility, and low openness to experience have higher levels of economic anxiety, as do those with high levels of neuroticism, perceived vulnerability to illness, and attribution from large group activities ( Mann et al, 2020 ). People with mental and physical health conditions may have higher levels of depression and anxiety because they are more likely to be unemployed and are prone to have higher levels of depression and anxiety ( Hao et al, 2020 ; Kwong et al, 2020 ; Jung et al, 2021 ). Extreme loneliness is the main cause of psychological distress ( Mikocka-Walus et al, 2021 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Social protection measures include daily demand provision and social support ( Jung et al, 2021 ) and cash transfer programs ( Bauer et al, 2021 ). Future research should examine how to effectively use social protection measures (or relief plans) to solve the short-term and long-term effects of economic uncertainty caused by large-scale epidemics or economic crises on mental health.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Furthermore, they feel significantly less supported by their social environment. However, social support acts as a protective factor against psychological burden from the pandemic in non-infected individuals with preexisting depression, according to a prospective cohort study ( n = 1,928) ( 48 ). This patient group benefits particularly from external support in the context of the SARS-CoV-2 pandemic ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, social support acts as a protective factor against psychological burden from the pandemic in non-infected individuals with preexisting depression, according to a prospective cohort study ( n = 1,928) ( 48 ). This patient group benefits particularly from external support in the context of the SARS-CoV-2 pandemic ( 48 ). In contrast, our study identified that psychologically burdened infected respondents failed to use sufficient adaptive coping strategies, such as maintaining social contacts, adhering to a daily structure, and getting adequate sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has affected both the physical and mental health of frontline health workers (HCWs). Mental health problems have been reported among these HCWs irrespective of any history of psychologic illness in the past (1)(2)(3). One metaanalysis conducted in Asian countries during the COVID-19 crisis showed that more than 20% of people developed anxiety and depression (4).…”
Section: Introductionmentioning
confidence: 99%